EVALUASI PENYALURAN BANTUAN KREDIT BERGULIR PADA USAHA KECIL DAN MENENGAH DI KECAMATAN TERING KABUPATEN KUTAI BARAT - Ainun Jariah; Masjaya .; Djumadi . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this research is to describe and evaluate the distribution of soft loan on small and medium enterprises in Tering District West Kutai, as well as to find the factors that support and hinder the enterprise. This research uses a qualitative descriptive with Interactive Model developed by Miles and Huberman, while research conducted in the District Tering. From the research it is showed that, not all small and medium businesses could take advantage of this assistance.